CHURCH GOVERNANCE CHURCH GOVERNANCE IN THE CHRISTIAN CIRCLES OR PERSPECTIVE RATIONALE& JUSTIFICATION (This helps us detail the aims and objectives of this course/lessons.) - N MBURU, REV GEORGE (IJRDO - Journal of Social Science and Humanities Research, 2016)
This helps us to explore the whole debate about Church Government and all it entails.One need to understand what governance really is and how it ought to be conducted in a Christian leadership mindset. Though God ALMIGHTY IS THE Sovereign leader with all authority and power he leads the kingdoms of men with wisdom, unsearchable understanding and also has power and might. Every other leadership and governance needs to take cognizance of this. This therefore will help us explore the following objectives: